flaA-SVR Based Genetic Diversity of Multiresistant Campylobacter jejuni Isolated From Chickens and Humans - Wieczorek, Kinga; Wołkowicz, Tomasz; Osek, Jacek (Frontiers in Microbiology, 2019)
Campylobacter jejuni is one of the most common causes of human foodborne bacterial infections worldwide. The objective of this study was to assess the molecular diversity, using flaA sequencing, of 602 C. jejuni isolated from chicken food chain, i.e. chicken feces (n = 151), chicken carcasses (n = 150), chicken meat (n = 150) and from humans (n = 151) and to determine antimicrobial multiresistant profiles of the isolates as well as to analyze the relationship of the isolate genotypes with their antimicrobial resistance profiles and source of isolation. Multidrug resistant patterns were identified in 110 (18.3%) C. jejuni isolates recovered from all sources and most isolates were resistant to ciprofloxacin (CIP), nalidixic acid (NAL), streptomycin (STR), and tetracycline (TET) (92; 15.3%) or ciprofloxacin, streptomycin, and tetracycline (13; 2.2%). Only a few isolates were multiresistant to ciprofloxacin, nalidixic acid, tetracycline, and erythromycin (3; 0.5%) or ciprofloxacin, nalidixic acid, streptomycin, tetracycline, and erythromycin (2; 0.3%). A total of 79 flaA-SVR subtypes were identified, including 40 (50.6%) unique to the isolates' origins, with the most common sequence types 16, 54, 36, 34, and 287 which covered 56 (9.3%), 50 (8.3%), 48 (8.0%), 35 (5.8%), and 32 (5.3%) of C. jejuni isolates, respectively. It was found that 13 isolates had the novel flaA-SVR subtypes which were not present in the pubMLST database. These isolates were recovered from chicken feces (6 isolates), carcasses (2 isolates), meat (one isolate) and from humans (4 isolates). Multiresistant C. jejuni were classified into 26 different sequence subtypes. Among the most numerous multidrug resistant profile CIP+NAL+STR+TET 21 different flaA-SVR subtypes, with total of 92 isolates, were identified. Most of them were classified to 287 (18; 19.6% isolates), 100 (13; 14.1%), 34 (9; 9.8%), 208 (8; 8.7%), and 781 (8; 8.7%) molecular variants. Isolates resistant to CIP, STR and TET (13 isolates) were mainly from chicken feces (12 isolates) and classified into 5 flaA-SVR sequence types, with the most common 36 (8 isolates). The obtained results show a broad molecular diversity of multiresistant C. jejuni isolates and suggest chickens as a possible source of human Campylobacter infections in Poland.